2022
DOI: 10.1002/pd.6165
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from prenatal exome sequencing

Abstract: Background Prenatal exome sequencing (ES) for monogenic disorders in fetuses with structural anomalies increases diagnostic yield. In England there is a national trio ES service delivered from two laboratories. To minimise incidental findings and reduce the number of variants investigated, analysis uses a panel of 1205 genes where pathogenic variants may cause abnormalities presenting prenatally. Here we review our laboratory's early experience developing and delivering ES to identify challenges in interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
2
24
1
2
Order By: Relevance
“…Prenatal diagnosis may thus take great advantage of genotype‐first approaches although a definitive prenatal molecular diagnosis can only be reached if a robust correlation with the phenotype can be established. In accordance with others, 31 this case also stresses the importance of careful examination of (likely) pathogenic variants in dominant genes, even if inherited from apparently healthy parents.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Prenatal diagnosis may thus take great advantage of genotype‐first approaches although a definitive prenatal molecular diagnosis can only be reached if a robust correlation with the phenotype can be established. In accordance with others, 31 this case also stresses the importance of careful examination of (likely) pathogenic variants in dominant genes, even if inherited from apparently healthy parents.…”
Section: Discussionsupporting
confidence: 87%
“…Prenatal robust correlation with the phenotype can be established. In accordance with others, 31 this case also stresses the importance of careful examination of (likely) pathogenic variants in dominant genes, even if inherited from apparently healthy parents.…”
Section: Discussionsupporting
confidence: 87%
“…Clinical diagnostic yield was relatively low at 10–12% overall. Selection of cases using a ‘pre-test’ multidisciplinary team (including a Clinical Geneticist) and careful ‘targeting’ of specific fetal phenotypes may significantly increase diagnostic rate to over 30% [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for analyzing data, such as inheritance filtering, can limit the results obtained. 23 Two studies compare results from sequencing on neonates to what could have been detected prenatally if we had more access to sequencing and better strategies to analyze the data and show that many conditions could be diagnosed earlier. 24,25 Moreover, at least one study showed that even for fetuses with no observable structural anomalies, P and LP variants can be detected.…”
mentioning
confidence: 99%
“…Finally, our tools and knowledge to gain all the potential benefits from sequencing are still incomplete. Strategies for analyzing data, such as inheritance filtering, can limit the results obtained 23 . Two studies compare results from sequencing on neonates to what could have been detected prenatally if we had more access to sequencing and better strategies to analyze the data and show that many conditions could be diagnosed earlier 24,25 .…”
mentioning
confidence: 99%